Soybean Cost-Return Budget in Northeast Kansas - Fogleman, Sarah L.; Duncan, Stewart R. (My University, 2007)
This publication projects a budget that reflects expected income and costs based on typical soybean production practices in northeastern Kansas.
MF570_2007_10
Keywords: MF570; Economics; Crops; MF